Associations between COVID-19 Vaccination Status and Self-Reported SARS-CoV-2 Infection among 8538 Children Aged 3–17 Years during a Massive COVID-19 Outbreak after China Changed Its Zero-COVID-19 Policy: A Cross-Sectional Survey - Lixian Su; Siyu Chen; Hongbiao Chen; Yuan Fang; Weijun Peng; Xiaofeng Zhou; Jingwei Luo; Xue Liang; Kechun Zhang; Zixin Wang (Vaccines, 2023)
This study aimed to investigate the associations between COVID-19 vaccination status and self-reported SARS-CoV-2 infection among children and adolescents aged 3–17 years during a massive COVID-19 outbreak after China changed its zero COVID policy. A cross-sectional online survey was conducted between 1 and 9 March 2023. Participants were the parents of children studying in kindergartens, primary schools, or secondary schools in Shenzhen. Convenient sampling was used. All kindergartens, primary schools, and secondary schools in the Longhua District of Shenzhen invited the parents of children and adolescents attending the schools. Interested parents completed an online survey. Multivariate logistic regression was fitted. Among 8538 participants, 40.9% self-reported that their children had SARS-CoV-2 infection after 7 December 2022, where 92.9% of them received two doses of the COVID-19 vaccines, and 74.6% received their second dose for more than six months. In multivariate analysis, children who received their second dose of the COVID-19 vaccination for no more than three months had a lower SARS-CoV-2 infection rate compared to unvaccinated children (<1 month: AOR: 0.17, 95% CI: 0.07, 0.44; 1–3 months: AOR: 0.54, 95% CI: 0.41, 0.75). The duration of protection conferred by the primary COVID-19 vaccination series was relatively short among children. A booster dose should be considered for children.